Avaliação do estado de implementação da construção enxuta em uma obra brasileira - Rodegheri, Priscila Mirapalhete; Serra, Sheyla Mara Baptista; Lorenzon, Itamar Aparecido (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
Lean Construction (LC) is an important management philosophy and its efficiency should be measured as well as another management strategy. Many Measurement Models (MM) can be found to indicate company maturity in LC, however just few of them is suitable for each scenario. In this paper, a case study is carried out applying one international MM in one Brazilian project to verify its suitability. The selected MM were developed by American Community of Practice of Lean Construction Institute (LCI), called LCI Lean IPD Health and Maturity Assessment Tool. This MM were considered proper to this project context and providing a guideline to improve LC.